2023
DOI: 10.1002/srin.202200902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempering Temperature on the Microstructure, Deformation and Fracture Properties of an Ultrahigh Strength Medium‐Mn Steel Processed by Quenching and Tempering

Abstract: Herein, a medium‐Mn steel containing 4 wt% Mn is designed to achieve ultrahigh tensile strength and good ductility by the quenching and tempering process. The effects of tempering temperature on the microstructure, tensile behavior, and fracture properties under different stress states are explored. It is observed that tempering temperature influences the fracture mechanisms of the ultrahigh‐strength steels. Both ductile fracture strain and cleavage fracture strength of the investigated medium‐Mn steel are aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…[10] Besides, some studies confirmed that medium-Mn steels were ideal materials to achieve RA present in the martensite matrix via hot stamping process. [11,12] However, the tensile ductility of most hot-stamped medium-Mn steels without baking or tempering treatment was terrible, [13,14] which may be related to the brittleness of martensite in the hot-stamped medium-Mn steels. In contrast, superior tensile ductility was achieved in warm-stamped medium-Mn steels with the microstructure consisting of RA, ferrite, and martensite, which was processed by low-temperature rolling, heat treatment at intercritical temperature region, and warm stamping (without baking/tempering treatment).…”
Section: Introductionmentioning
confidence: 99%
“…[10] Besides, some studies confirmed that medium-Mn steels were ideal materials to achieve RA present in the martensite matrix via hot stamping process. [11,12] However, the tensile ductility of most hot-stamped medium-Mn steels without baking or tempering treatment was terrible, [13,14] which may be related to the brittleness of martensite in the hot-stamped medium-Mn steels. In contrast, superior tensile ductility was achieved in warm-stamped medium-Mn steels with the microstructure consisting of RA, ferrite, and martensite, which was processed by low-temperature rolling, heat treatment at intercritical temperature region, and warm stamping (without baking/tempering treatment).…”
Section: Introductionmentioning
confidence: 99%